Encyclopedia of Russian and Slavic myth and legend - Dixon-Kennedy, Mike 1958- (ABC-CLIO, 1998)
Covers the myths and legends of the Russian Empire at its greatest extent as well as other Slavic people and countries. Includes historical, geographical, and biographical background information.